2013
DOI: 10.1111/1541-4337.12048
|View full text |Cite
|
Sign up to set email alerts
|

Development and Control of Bacterial Biofilms on Dairy Processing Membranes

Abstract: Membrane fouling is a major operational problem that leads to reduced membrane performance and premature replacement of membranes. Bacterial biofilms developed on reverse osmosis membranes can cause severe flux declines during whey processing. Various types of biological, physical, and chemical factors regulate the formation of biofilms. Extracellular polymeric substances produced by constitutive microflora provide an effective barrier for the embedded cells. Cultural and microscopic techniques also revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 231 publications
(136 reference statements)
2
51
0
Order By: Relevance
“…At the morphological level, ESEM imaging showed that, non-submerged biofilms often displayed homogeneous matrix, previously reported to be less stable compared to their heterogeneous counterparts (Anand et al, 2014), enhancing the risk of cell dissemination into processing environments. These findings are interesting cues for the dairy industry.…”
Section: Discussionmentioning
confidence: 93%
“…At the morphological level, ESEM imaging showed that, non-submerged biofilms often displayed homogeneous matrix, previously reported to be less stable compared to their heterogeneous counterparts (Anand et al, 2014), enhancing the risk of cell dissemination into processing environments. These findings are interesting cues for the dairy industry.…”
Section: Discussionmentioning
confidence: 93%
“…However, even with daily care, long-term fouling of the membranes remains a major issue affecting the performance of membrane systems and leads to expensive membrane replacements (Jirjis and Luque 2010;Anand et al 2014). For most dairy fluids, short-and long-term fouling results from the accumulation of proteins (Bégoin et al 2006) and minerals (Anand et al 2014) on membrane surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…For most dairy fluids, short-and long-term fouling results from the accumulation of proteins (Bégoin et al 2006) and minerals (Anand et al 2014) on membrane surfaces. However, concerns around bacterial adhesion warrant further investigation in the dairy industry because of the great resilience of biofilms exposed to cleaning procedures (Tang et al 2009;Hassan et al 2010;Anand et al 2012;Anand and Singh 2013;Anand et al 2014) and the high bacterial counts observed in filtered products (Anand et al 2012). Biofouling, through biofilm development, has been reported in desalination plants (Matin et al 2011;Khan et al 2013;Levi et al 2016) and membrane bioreactors (Ivnitsky et al 2007;Malaeb et al 2013;Vanysacker et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a relevant strategy for removing biofilms from industrial systems is to employ enzymes. Indeed, these have been used for the treatment of biofilms formed in food areas (Anand, Singh, Avadhanula, & Marka, 2014;Lequette, Boels, Clarisse, & Faille, 2010).…”
mentioning
confidence: 99%